1996
DOI: 10.1007/bf00054016
|View full text |Cite
|
Sign up to set email alerts
|

Role of intermediate filaments in migration, invasion and metastasis

Abstract: The expression of intermediate filament proteins is remarkably tissue-specific which suggests that the intermediate filament (IF) type(s) present in cells is somehow related to their biological function. However, in some cancers-particularly malignant melanoma and breast carcinoma, there is a strong indication that vimentin and keratin IFs are coexpressed, thus presenting as a dedifferentiated or interconverted (between epithelial and mesenchymal) phenotype. In this review, two in vitro models are presented wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
169
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(188 citation statements)
references
References 84 publications
13
169
0
2
Order By: Relevance
“…Direct evidence showed the relation between the expression of CK19 and increased migratory and invasive activity in some tumors 23,24 ; other research found that the immune activity of CK19 and anti-CK19 autoantibody could be responsible for the degrading of basement membrane. 7 Another study found that CK19 was correlated with vascular invasion in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence showed the relation between the expression of CK19 and increased migratory and invasive activity in some tumors 23,24 ; other research found that the immune activity of CK19 and anti-CK19 autoantibody could be responsible for the degrading of basement membrane. 7 Another study found that CK19 was correlated with vascular invasion in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hours of incubation at 37°C, the cells that invaded each membrane were collected, stained, and counted as previously described. 23 Percent invasion was corrected for proliferation and calculated as follows:…”
Section: Invasion Assaymentioning
confidence: 99%
“…19 Based on the observation that DLKP cells express vimentin but not cytokeratin-18, 20 immunofluorescence analysis was carried out to investigate any changes in cytokeratin-18 or vimentin levels. No changes were observed in the DLKP variants (data not shown).…”
Section: Immunofluorescence Of Cytokeratin-18 and Vimentinmentioning
confidence: 99%